A Validated HPLC-DAD Method for Simultaneous Determination of Etodolac and Pantoprazole in Rat Plasma - Ali S. Abdelhameed; Samar A. Afifi (Journal of Chemistry)
A simple, sensitive, and accurate HPLC-DAD method has been developed and validated for the simultaneous determination of pantoprazole and etodolac in rat plasma as a tool for therapeutic drug monitoring. Optimal chromatographic separation of the analytes was achieved on a Waters Symmetry C18 column using a mobile phase that consisted of phosphate buffer pH~4.0 as eluent A and acetonitrile as eluent B in a ratio of A : B, 55 : 45 v/v for 6 min, pumped isocratically at a flow rate of 0.8 mL min−1. The eluted analytes were monitored using photodiode array detector set to quantify samples at 254 nm. The method was linear with r2=0.9999 for PTZ and r2=0.9995 for ETD at a concentration range of 0.1–15 and 5–50 μgmL−1 for PTZ and ETD, respectively. The limits of detection were found to be 0.033 and 0.918 μgmL−1 for PTZ and ETD, respectively. The method was statistically validated for linearity, accuracy, precision, and selectivity following the International Conference for Harmonization (ICH) guidelines. The reproducibility of the method was reliable with the intra- and interday precision (% RSD) <7.76% for PTZ and <7.58 % for ETD.